Pengaruh Penerapan Pembelajaran Berdiferensiasi Dan Model Storytelling Terhadap Hasil Belajar Melalui Keterampilan Sosial Emosional Siswa Sekolah Dasar - Agung Budi Sedayu; Kadeni Kadeni; Imam Sukwatus Suja’i (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2025)
This study analyzes the effect of differentiated instruction and the storytelling model on student learning outcomes through social-emotional skills in social studies learning for fourth-grade students at SDN 1 Kampungdalem. Using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method, this research explores the relationships between these variables. The results indicate that differentiated instruction and storytelling significantly influence students' social-emotional skills, which act as a mediator in improving learning outcomes. However, neither has a direct significant effect on learning outcomes. This suggests that strengthening social-emotional skills can be a key factor in enhancing students' academic achievement. These findings highlight the importance of instructional strategies that focus not only on academics but also on the development of social-emotional skills. Teachers are encouraged to optimize differentiated instruction and integrate storytelling with other methods. Schools are advised to provide teacher training and develop programs that support students' social-emotional skills. Future research can explore other factors influencing learning outcomes and adopt more in-depth research approaches.